2013
DOI: 10.1073/pnas.1301125110
|View full text |Cite
|
Sign up to set email alerts
|

Forebrain dopamine neurons project down to a brainstem region controlling locomotion

Abstract: The contribution of dopamine (DA) to locomotor control is traditionally attributed to ascending dopaminergic projections from the substantia nigra pars compacta and the ventral tegmental area to the basal ganglia, which in turn project down to the mesencephalic locomotor region (MLR), a brainstem region controlling locomotion in vertebrates. However, a dopaminergic innervation of the pedunculopontine nucleus, considered part of the MLR, was recently identified in the monkey. The origin and role of this dopamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
83
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 42 publications
3
83
1
Order By: Relevance
“…We are thus confident that DA release in the MLR of rats is also evoked by the recruitment of dopaminergic cell bodies in the SNc and RRF, even though only electrical stimulation was used. Importantly, we found that the time-scale of DA release in the MLR was highly correlated with the activation of brainstem locomotor networks, as previously reported in lampreys (22).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…We are thus confident that DA release in the MLR of rats is also evoked by the recruitment of dopaminergic cell bodies in the SNc and RRF, even though only electrical stimulation was used. Importantly, we found that the time-scale of DA release in the MLR was highly correlated with the activation of brainstem locomotor networks, as previously reported in lampreys (22).…”
Section: Discussionsupporting
confidence: 87%
“…Electrical stimulation not only activates cell bodies but also axons of passage. In some experiments in salamanders, we used chemical stimulation to circumvent the effect of activating en passant fibers, and the results were the same, as previously reported with similar control experiments in lampreys (22). We are thus confident that DA release in the MLR of rats is also evoked by the recruitment of dopaminergic cell bodies in the SNc and RRF, even though only electrical stimulation was used.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations